"Survivor heroes" and rising heroes - Povedák, István (Traditiones (Ljubljana), 2014)
Author illustrates the phenomenon where some socialist heroes ("survivors") have not disappeared together with their fellows, but have remained popular with the examples of the cult of János Kádár and Imre Nagy in Hungary.
Keywords: history; Kádár, János, 1912-1989; Nagy, Imre, 1896-1958; personalities; socialism; zgodovina; znamenite osebnosti; Hungary; socializem; narodna identiteta; Madžarska